Exploration of Earth’s Magnetosphere Using CubeSats with Electric Propulsion - Alessandro A. Quarta (Aerospace)
The study of the Earth’s magnetosphere through in situ observations is an important step in understanding the evolution of the Sun–Earth interaction. In this context, the long-term observation of the Earth’s magnetotail using a scientific probe in a high elliptical orbit is a challenging mission scenario due to the alignment of the magnetotail direction with the Sun–Earth line, which requires a continuous rotation of the apse line of the spacecraft’s geocentric orbit. This aspect makes the mission scenario particularly suitable for space vehicles equipped with propellantless propulsion systems, such as the classic solar sails which convert the solar radiation pressure into propulsive acceleration without propellant expenditure. However, a continuous rotation of the apse line of the osculating orbit can be achieved using a more conventional solar electric thruster, which introduces an additional constraint on the duration of the scientific mission due to the finite mass of the propellant stored on board the spacecraft. This paper analyzes the potential of a typical CubeSat equipped with a commercial miniaturized electric thruster in performing the rotation of the apse line of a geocentric orbit suitable for the in situ observation of the Earth’s magnetotail. The paper also analyzes the impact of the size of a thruster array on the flight performance for an assigned value of the payload mass and the science orbit’s characteristics. In particular, this work illustrates the optimal guidance laws that allow us to maximize the duration of the scientific mission for an assigned CubeSat’s configuration. In this sense, this paper expands the literature regarding the study of this interesting mission scenario by extending the study to conventional propulsion systems that use a propellant to provide a continuous and steerable thrust vector.